Diagnostic delay in inflammatory bowel disease increases the risk of intestinal surgery - Lee, Dong-Won; Koo, Ja Seol; Choe, Jung Wan; Suh, Sang Jun; Kim, Seung Young; Hyun, Jong Jin; Jung, Sung Woo; Jung, Young Kul; Yim, Hyung Joon; Lee, Sang Woo (World journal of gastroenterology : WJG, 2017)
To investigate the factors affecting diagnostic delay and outcomes of diagnostic delay in inflammatory bowel disease (IBD). We retrospectively studied 165 patients with Crohn's disease (CD) and 130 patients with ulcerative colitis (UC) who were diagnosed and had follow up durations > 6 mo at Korea University Ansan Hospital from January 2000 to December 2015. A diagnostic delay was defined as the time interval between the first symptom onset and IBD diagnosis in which the 76 to 100 percentiles of patients were diagnosed. The median diagnostic time interval was 6.2 and 2.4 mo in the patients with CD and UC, respectively. Among the initial symptoms, perianal discomfort before di-agnosis (OR = 10.2, 95%CI: 1.93-54.3, = 0.006) was associated with diagnostic delays in patients with CD; however, no clinical factor was associated with diagnostic delays in patients with UC. Diagnostic delays, stricturing type, and penetrating type were associated with increased intestinal surgery risks in CD (OR = 2.54, 95%CI: 1.06-6.09; OR = 4.44, 95%CI: 1.67-11.8; OR = 3.79, 95%CI: 1.14-12.6, respectively). In UC, a diagnostic delay was the only factor associated increased intestinal surgery risks (OR = 6.81, 95%CI: 1.12-41.4). A diagnostic delay was associated with poor outcomes, such as increased intestinal surgery risks in patients with CD and UC.